Low energy, wind catcher assisted indirect-evaporative cooling system for building applications - Elzaidabi, Abdalla Ali Mohamed (2009)
Increased consciousness of the environmental problems has aroused people’s interest of renewable energy systems, especially the application of green features in buildings. The demand for air conditioning / cooling in domestic and non-domestic buildings is rising throughout the world; this increases the reliance on conventional fuels and the global warming effect from greenhouse gas emissions. Passive cooling and energy efficient design can substantially reduce reliance on fuel based heating and cooling. Passive and Hybrid Downdraught Cooling, in different forms, is now technically viable in many parts of the world. This has been established through a combination of research projects. In some hot arid regions, a major part of the energy consumed consists of air-conditioning requirements. Alternative methods, using passive cooling techniques, can assist in reducing the conventional energy consumption in buildings. Evaporative cooling, which can be tracked back several hundreds of years in ancient Egypt and Persia [1–3], is one of the most effective strategies, because of the enormous latent heat needed for evaporation of water. Green features are architectural features used to mitigate migration of various air-borne pollutants and transmission of air from outside to indoor environment in an advantageous way [9].